UAV-Based Thermal Mapping for Urban Heat Island Intensity Assessment in Malang, Indonesia - Wardoyo, Jono; Iyati, Wasiska; Citraningrum, Andika (Civil and Environmental Science Journal (CIVENSE), 2025)
Urban Heat Island (UHI) poses a growing environmental and public health challenge, particularly in densely populated urban areas with limited green infrastructure. High-density settlements often experience extreme thermal stress due to compact building forms, poor ventilation, and heat-retaining materials, yet lack detailed spatial data to guide mitigation efforts. This study employed UAV-mounted thermal imaging to map and analyze surface temperature distribution across two contrasting residential zones. Results showed that Zone 1, characterized by tightly packed housing and metal roofing, experienced the most severe UHI effect, with 87.64% of its area exceeding 35°C by 15:00. In contrast, Zone 2, with slightly more vegetation and open layout, recorded 83.87% above 35°C at the same time. These findings highlight the significant impact of urban morphology and land cover on thermal performance. This research contributes a high-resolution, drone-based methodology for assessing micro-scale UHI patterns, offering a practical tool for climate-responsive urban planning.